2021
DOI: 10.1128/msphere.00658-21
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus F317L Protein Inhibits NF-κB Activation To Evade Host Immune Response and Promote Viral Replication

Abstract: African swine fever (ASF) is one of the most important pig diseases, causing a high case fatality rate and trade restrictions upon reported outbreaks. The limited understanding of the functions of the proteins of the causative agent, African swine fever virus (ASFV), has become a primary barrier to developing available commercial ASFV vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…pF317L consists of 317 amino acids, and its function is still unknown ( Dixon et al., 2013 ). A recent report shows that pF317L is an inhibitor of the inflammatory responses ( Yang et al., 2021 ). pF317L inhibits TNFα and poly(dA:dT)-induced proinflammatory cytokine expression and NF-κB promoter activation.…”
Section: Escape From Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…pF317L consists of 317 amino acids, and its function is still unknown ( Dixon et al., 2013 ). A recent report shows that pF317L is an inhibitor of the inflammatory responses ( Yang et al., 2021 ). pF317L inhibits TNFα and poly(dA:dT)-induced proinflammatory cytokine expression and NF-κB promoter activation.…”
Section: Escape From Innate Immunitymentioning
confidence: 99%
“…Naturally, p317L also inhibits p65 nuclear translocation. It is found that the amino acids from 109 to 208 in pF317L are critical for its interaction with IKKβ and the suppression of NF-κB activation ( Yang et al., 2021 ). Importantly, deletion of F317L from ASFV is lethal to the virus.…”
Section: Escape From Innate Immunitymentioning
confidence: 99%
“…In 2020, Zhuo et al demonstrated that MGF360-12L can block the interaction between p65 and KPNA2, KPNA3, and KPNA4, and can interfere with the nuclear translocation of NF-κB [ 43 ]. Five immunosuppressive genes were reported in 2021, including E120R, F317L, MGF505-7R, MGF505-11R, and I215L [ 44 , 45 , 46 , 47 , 48 , 49 ]. E120R can interact and block the activation of IRF3, thereby inhibiting the expression of IFN-β [ 44 ].…”
Section: The Major Defense Mechanisms and Asfv Interactionsmentioning
confidence: 99%
“…E120R can interact and block the activation of IRF3, thereby inhibiting the expression of IFN-β [ 44 ]. F317L inhibits IKKβ phosphorylation, thereby reducing the phosphorylation and ubiquitination of IkBα, thereby inhibiting the activation of the NF-κB pathway [ 45 ]. Li et al reported that MGF-505-7R promoted the expression of autophagy-related protein ULK1 to degrade STING, and inhibited IFN-γ-mediated JAK1 and JAK2-mediated signaling pathways [ 46 , 48 ].…”
Section: The Major Defense Mechanisms and Asfv Interactionsmentioning
confidence: 99%
“…A528R inhibits TLR8-NF-kB signaling by targeting p65 activation and nuclear translocation (Liu X. et al, 2021). F317L interacts with IkB kinase b (IKKb) and impairs NF-kB pathway activation by disrupting NF-kB activity to evade the host immune response (Yang J. et al, 2021). ASFV MGF360-14L has been selected as target gene of deletion for attenuated ASF vaccine development, yet its function is still unclear.…”
Section: Introductionmentioning
confidence: 99%